2011
DOI: 10.1152/ajpendo.00426.2011
|View full text |Cite
|
Sign up to set email alerts
|

Signal integration at the level of ion channel and exocytotic function in pancreatic β-cells

Abstract: MacDonald PE. Signal integration at the level of ion channel and exocytotic function in pancreatic ␤-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 66 publications
2
34
0
Order By: Relevance
“…Other studies have not reported differences, probably because ob/ob islets were stimulated by glucose concentrations (20 mM) at which β-cells were maximally depolarized (Fournier et al, 1993). In contrast to the glucose effects, no differences were found by KCl stimulation, which further supports the idea that increased Ca 2+ signals in ob/ob islets may be mediated by changes in glucose metabolism or metabolicrelated factors (Ivarsson et al, 2005;MacDonald, 2011;Rorsman and Braun, 2013), particularly at low-intermediate glucose levels. The idea that metabolism could be affected in ob/ob islets was also supported by the higher response to KIC.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Other studies have not reported differences, probably because ob/ob islets were stimulated by glucose concentrations (20 mM) at which β-cells were maximally depolarized (Fournier et al, 1993). In contrast to the glucose effects, no differences were found by KCl stimulation, which further supports the idea that increased Ca 2+ signals in ob/ob islets may be mediated by changes in glucose metabolism or metabolicrelated factors (Ivarsson et al, 2005;MacDonald, 2011;Rorsman and Braun, 2013), particularly at low-intermediate glucose levels. The idea that metabolism could be affected in ob/ob islets was also supported by the higher response to KIC.…”
Section: Discussionsupporting
confidence: 51%
“…4) would be also associated with the improved mitochondrial activity. In addition to electrical and Ca 2+ signaling effects, it has been shown that ATP and other glucose-stimulated mitochondrial factors like glutamate and, particularly, NAD(P)H can also exert a positive regulation of exocytosis and secretory granule mobilization (Ivarsson et al, 2005;MacDonald, 2011;Maechler and Wollheim, 1999; Reinbothe et al, 2009; Rorsman and Braun, 2013). Thus, all these cellular events are expected to be augmented in ob/ob β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Punctate staining intensity, which increases as exocytic sites assemble, is enhanced by transcellular CADM1 interactions in both neural processes and, as now revealed here, in ␤-cells (3,7,13,46). Transcellular CADM1 interactions likely promote assembly of the submembrane ␤-cell secretory complexes, sometimes referred to as "excitosomes," at sites of ␤-cell-to-␤-cell contact (37,43). CADM1 functions in this regard similarly to neurexin, which is also expressed in both ␤-cells and brain (40).…”
Section: Discussionsupporting
confidence: 60%
“…Seminal studies in the 1990s demonstrated an additional "K ATP -independent" or "amplifying" action of glucose that is required for optimal secretion (9)(10)(11) and controls the amplitude of the secretory response (2). The prevailing evidence suggests that this metabolic amplification of insulin secretion occurs distally in the secretory pathway, possibly at the exocytotic site (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%